Differences in the Knowledge of Pregnant Women About Nutrition During the Covid-19 Pandemic with Leaflet Media Video Media at the Meureubo Health Center, Meureubo District, West Aceh Regenc - Yushida Yushida; Gustiana Gustiana; Cut Nurhasanah (Institute of Computer Science (IOCS), 2022)
The Coronavirus pandemic has impacted the health sector, including the nutritional status of pregnant women. The low level of knowledge of pregnant women about nutrition is one of the causes of malnutrition. The nutritional status of pregnant women before and during pregnancy can affect the growth of the fetus being conceived. This study aimed to determine the knowledge of pregnant women about nutrition during the Covid-19 period using the leaflet and video method at the Meureubo Health Center, Meureubo District, West Aceh Regency. Research design The study design was cross-sectional. The sample of this study was 72 people who were taken using the accidental sampling technique. The analysis was used in the univariate analysis and bivariate analysis. The results showed that the video media and leaflet media influenced the knowledge of pregnant women about nutrition during the covid 19 pandemics at the Meureubo Health Center